Studies on pygmy grasshoppers: Redescription of the male and description of the female of Metrodora rana Bolívar, 1887 (Orthoptera: Tetrigidae) with new records to Colombia and Brazil - Cadena-Castañeda, Oscar J.; Alvarez, Edna Jhinela Moreno; Quintana-Arias, Ronald Fernando; García, Alexander García; Tavares, Gustavo Costa (Zootaxa, 2025)
In this contribution to the study of pygmy grasshoppers, the description of the female of Metrodora rana Bolívar, 1887 is provided as well as the redescription of the male with additional characters to those included in its original description. The occurrence in the Colombian and Brazilian Amazon is recorded for the first time, and additional iNaturalist records from Peru and Brazil are also presented. The importance of the study of M. rana for the foundations of the classification of the subfamily Metrodorinae is discussed. Additionally, Metrodora ala Kasalo & Skejo, 2025 syn. nov. is synonymized under Hebardidora kasaloi Cadena-Castañeda & Tavares, 2025, and Metrodora mollilobata Kasalo & Skejo, 2025 syn. nov. under Hebardidora harroweri (Hebard, 1924).